CREDIT SCORING AND THE CONSTRUCTION - Lightfoot, Neil (My University, 2011)
Automated credit application scoring is integral to lending money. For banks credit application scoring provides a mechanism for managing risk and hence profit: for borrowers it means immediate access to goods and services which might only have been accessible in the future. For borrowers, therefore, access to credit fundamentally shapes their every existence. Whereas all previous research exploring the unintentional effects of credit scoring has focused on its discriminatory effects, the main purpose of this study was to explore how borrower identity is unintentionally constructed through the credit scoring technologies of a retail bank. With a view towards constructing different borrower identities, it moreover proposed alternative scorecard characteristics which hitherto might not have been explored. The study was wholly explorative and thus qualitative in nature. Critical ethnography was used as the principle method of analysis and means of interpretation. The main findings were that there are three broad sources of credit scoring characteristics and that these characteristics are associated with, not causative of, borrower riskiness. In addition, a non-exhaustive list of four assumptions underpinning credit scoring and scorecards and seven assumptions, which are made about borrowers by scorecard practitioners, were identified. As a consequence of these assumptions it was argued that there are groups of borrowers who are unintentionally excluded through credit scoring. Two primary consequences of credit exclusion were entertained and finally, some few alternative scorecard characteristics were proposed. Collectively these findings support the view that borrower identity is systematically fabricated on an ongoing basis through the naïve application of processes, systems and technologies of credit scoring practitioners. It was also argued that the future of application scorecard building would iii see more advanced variables being used which will give rise to a selfregulating borrower, less overtly disciplinary banks, and more pervasive credit bureaux.
MBA - WBS
Keywords: Credit scoring; Banks and banking